Associations between diet and acne lesions - Magdalena Daszkiewicz (National Institute of Public Health - National Institute of Hygiene, 2021)
Acne is one of the most common dermatological conditions affecting millions of people worldwide. It is assumed that the main etiological factors acne are considered to be the excessive production of sebum and hormones, and the colonisation of P. acnes bacteria. The relationship between diet and acne lesions is still the subject of debate and scientific criticism. On the one hand, studies suggest that an elimination diet is of no benefit in the treatment of acne, while other studies indicate that there is a close a close relationship between diet and the occurrence of acne lesions. Already in the 1970s, some scientists claimed that the course of acne could be modified by specific dietary components. Several studies have confirmed, among others, the role of a diet with a high glycemic index diet in acne exacerbation and suggested that a low glycemic index diet for several weeks may lead to a reduction in the number of acne lesions. The effect of milk consumption was also investigated in terms for its potential role in acne pathogenesis, including its ability to increase insulin levels. In the last decade, studies have also emerged to determine the effect of dark chocolate on the exacerbation of acne symptoms. To date, it has not been conclusively established which component of chocolate may have a potentially adverse effects on the course of acne. The article summaries the current knowledge on the relationship between diet and acne lesions, and discusses the results of recent studies on selected dietary components that may exacerbate acne.